Airborne Priapism: A Case of Nonischemic Priapism After Military Static-Line Parachute Injury. Issue 7 (1st July 2015) - Charny, Grigory; Booms, Zachary; McDonough, Patrick; Schauer, Steven
ABSTRACT: We report the case of a 21-year-old active duty U.S. Army soldier with painful and nonresolving priapism following blunt pelvic and lower extremity trauma from military static-line parachute injury during training. The patient's condition was initially managed with corporal aspiration and intracavernosal injections of phenylephrine that provided temporary relief but recurrence soon after. Referral to Urology at the site of the patient's injury yielded a diagnosis of penile hematoma. On subsequent evaluation by Urology on return to the patient's home duty station (over 96 hours after injury, with symptoms persisting), the corpora cavernosa were rigid, the corpus spongiosum was soft, and corporal blood gas drawn by the emergency department consistent with arterial blood. Penile duplex ultrasound revealed an isolated arterial-cavernosal fistula within the proximal left corporal body. The patient underwent percutaneous embolization of the fistula with successful resolution of his condition and return of normal erectile function. We discuss this unique case of high-flow priapism occurring after blunt trauma from military parachute injury and review suggested management in a stepwise fashion. The case is significant in that extensive literature review yields no previously described case of priapism following trauma from military parachute injury.